PERFORMANCE OF AGRICULTURE SECTOR IN BALI PROVINCE, 2013-2017 - Wulandira Sawitri Djelantik; Ida Ayu Listia Dewi (Faculty of Animal and Agricultural Science, Diponegoro University, 2020)
The agricultural sector has a multifunctional role in the development of an area. Bali Province is one of the provinces in Indonesia that uses rural areas as a gateway to the agricultural sector that supports the tourism sector. The contribution of the agricultural sector in 2017 amounted to 13.07 percent of the GRDP of the Province of Bali, number two of the 17 sectors (the sector of providing accommodation and food and drink occupy the first position, amounting to 22.82 percent. The purpose of this study was to map the growth typology of each sector in the Province of Bali, and evaluated the performance of the agricultural sector in the Province of Bali from 2013-2017. The location of the study was conducted in the Province of Bali, carried out deliberately (purposive) with the consideration that there has been a very alarming increase in the conversion of agricultural land functions in the Province of Bali. The typology used is Klassen, LQ (Location Quotient, and DLQ (Dynamic Location Quotient). The results of this study are the agriculture, forestry, and fisheries sectors in quadrant II, namely the advanced but depressed sector, as a whole is a “prospective” agricultural sector, the sector it has a basic role during 2013-2017 but this sector does not have the potential to remain a base sector because the growth rate of the agricultural sector in Bali Province is slower than the national level.